Plasma of arc discharge between melting Cu- and Ni-electrodes - Veklich, A.N.; Kleshich, M.M.; Fesenko, S.O.; Boretskij, V.F.; Kryachko, L.A. (Вопросы атомной науки и техники, 2018)
The intensity of erosion processes of asymmetric single-component Cu and Ni electrodes of the free burning electric arc at current of 30 A is studied by measurements of a content metals vapour in plasma column. Optical emission spectroscopy was used to determine the radial distributions of plasma temperature and electron density in the middle section of a discharge gap. These experimentally obtained data were used in the calculation of equilibrium plasma composition. So, the evaporation intensity of each electrode material can be estimated in such indirect way.